An indirect testing approach for characterizing pressure profiles of compression bandages and hosiery. Issue 2 (1st February 2018) - Kwon, Cassandra; Hegarty, Meghan; Oxenham, William; Thoney-Barletta, Kristin; Grant, Edward; Reid, Lawrence
Abstract: As outlined in compression therapy literature, the performance of a compression textile can be characterized by its stiffness and interface pressure. In this study, an indirect approach for measuring pressure from a set of compression bandages and hosiery was developed, from which rigidity ( EI ) values were determined, and tension–elongation curves and pressure-elongation data were calculated. The calculated pressure values were compared against PicoPress sensor readings measured on 10 participants. Results showed that the correlation between both approaches varied among bandage and hosiery samples.